Зоогеографичеокие особенности фауны браконид (Hymеnoptera, Braconidae) Азербайджана - Абдинбекова, А.А. (Вестник зоологии, 1973)
The modern fauna of Azerbaijan is inhomogeneous by its composition and can be divided conditionally into 8 zoogeographic groups: Holarctic species 2, Panpaleoarctic species — 203. European species — 10, Mediterranean species — 45, Mediterannean-Cauca¬sian species — 21, steppe species — 6, Iran-Transcaucasian — 2 and conditionally endemic Trancaucasian species — 36.